PERANCANGAN KAPAL TANKER 8200 DWT DENGAN KECEPATAN 12 KNOT RUTE PELAYARAN MAKASSAR - AMBON - Nindya Koesherawati, (2020)
The design of the 8200 DWT tanker from Makassar to Ambon is assumed to be in accordance with the request of the owner who wants to load premium oil from Makasar TBBM and supplied to Wayame TBBM, Ambon. The role of sea transportation is expected to support balanced and balanced economic growth and social development in every region in Indonesia. This design is to support regional development in supporting oil products. However, at the end of 2018 there was a shortage of Premium fuel oil in Ambon sourced from www.inews.id. Although the distribution of oil products is still ongoing, this is due to one of them losing the tanker. This design uses a preliminary design using 2 methods, namely the Comparative Method of 2 comparative ships with DWT, the ship's speed, coefficients, and removal as well as the Trial and Error Method in order to obtain maximum results. 2 The comparative ships used are the Thun Galaxy and the Svetlana ship sourced from Veri Star. From the results of the calculation the principal size of the ship is LOA : 123,3 m , LPP : 117,74 m , LWL : 120,09 m , B : 16,07 m , H : 9,84 m , T : 6,65 m , Vs : 12 knot , dan CB : 0,81.